THE EFFECT OF ORGANISATIONAL CYNICISM ON EMPLOYEE PERFORMANCE: TESTING THE AFFECTIVE, COGNITIVE AND BEHAVIOURAL DIMENSIONS - N, DR AISHWARYA; C, DR AARTHY; P, MR SENTHILMURUGAN (The journal of contemporary issues in business and government, 2021)
Organisational cynicism is one of the understudied topics, which is being overlooked in organisations for a long period of time. This has three dimensions: cognitive-lack of sincerity, honesty in organisation; Affective: emotional and sentimental responses towards the workplace; and Behavioural: showing negative attitude within workplace. Moreover, it results in decreased motivation, interpersonal conflicts, absenteeism, low organisational commitment, and low efficiency, dissatisfaction in work, unethical behaviour and reluctance in organisational citizenship behaviour. The Antecedents and consequences of organisational cynicism can be taken into account while calculating the turnover of the employees, efficiency and overall productivity of the organisation. Organisational cynicism can also be considered as one of the important factors to study whether an employee is happy with their organisation, their team mates, managers and the organisational climate. This study compares this variable with the performance of the employees. In the previous studies, job satisfaction was studied as one of the consequences of the study. There are only a few literatures which study the impact of organisational cynicism on performance. And most of these researches were conducted in either teaching or banking industries across the world. In the last three decades, IT industry has been the most outsourced industry from India. This Industry also contributes about 7.7% towards the GDP in India. From the studies of the performance of the employees in the IT industry, it has showed that lack of proper leadership, over-timing,inefficiency of the manager were some of the major sources of stress to the employees. This links the external factors of performance with consequences of organisational cynicism, which is employee burnout. So it is about time that a study analyses whether there is existence of organisational cynicism in the Industry, and relate it to the performance of the employees and the demographic factors which might also contribute to it. A conceptual model of organizational cynicism was developed as a result. This study focuses on the IT employees from one of the major software Hubs in India, which is Bangalore.